Practices Reflecting Functional Communication Training for Students With or At Risk for Emotional and Behavioral Disorders: Systematically Mapping the Literature. (November 2018) - Hollo, Alexandra; Burt, Jonathan L.
Students with and at risk for emotional and behavioral disorders (EBD) often have unidentified co-occurring language deficits, but few studies have evaluated communication-based interventions for this population. Functional communication training (FCT) teaches a communicative response (CR) as a replacement for problem behavior. FCT is an evidence-based practice for students with intellectual and developmental disabilities; however, preliminary literature searches revealed limited evidence to support its use for students without developmental delays. We hypothesized researchers may use similar practices but different terminology to teach and reinforce functionally equivalent CRs. Therefore, we replicated systematic search procedures from previous reviews of functional assessment–based interventions (FABI) for students with or at risk for EBD in school settings and mapped intervention strategies incorporating features of FCT. Results identified 113 published reports describing FABI for 243 students. Subsequent screening and coding procedures revealed 43 (38.05%) of the studies included a CR in interventions for 77 students. Additional analyses revealed antecedent and consequent procedures included in interventions for 58 students mirrored those used in FCT. That is, approximately one in four interventions developed for students with or at risk for EBD included key elements of FCT, despite few references to the term FCT in published reports.